Implementasi Case Base Learning untuk Menilai Keterampilan Diagnosis Kondisi Depresi Mahasiswa Tingkat Akhir - Ferdiansyah, Muhammad; Yaksa, Rully Andi (Fakultas Dakwah dan Komunikasi, UIN Raden Fatah Palembang, 2023)
The purpose of this study was to evaluate students' skills in diagnosing depressive conditions in final year students through a case base learning learning model. This type of research uses evaluation research and the data presented is in the form of qualitative evaluation data. Data collection techniques use observation, interview, and documentation instruments. Validity checks use four criteria, namely (1) Trust Test, (2) Transferability Test, (3) Defendability Test, and (4) Conformity Test. Data analysis uses three activities, namely matchmaking patterns, explanations, and time series analysis. The results of the study found that students' skills in diagnosing students' depressive conditions are in good creteria, this is characterized by students' skill in compiling non-test instruments, having the ability to formulate questions with reference to 5W + 1H and being skilled in presenting data collected in the field, so it can be concluded that the case base learning learning model is highly recommended to hone students' critical thinking skills.